The Role of e-Marketing Design and Customer Involvement Capability on Business Performance and Competitive Advantage of MSMEs in Tangerang Raya - Fahmi, Khaerul; Limakrisna2, Nandan; Muharam, Hari (Faculty of Science and Technology University of Pramita Indonesia, 2024)
The aim of this research is to determine and analyze the influence of e-marketing design and customer involvement capability partially on competitive advantage. To determine and analyze the influence of e-marketing design, customer involvement capability and competitive advantage both partially and simultaneously on business performance. The method used is a quantitative method, the analysis used is confirmatory factor analysis (CFA) with a total of 200 respondents. Data analysis using Lisrel 8.70 Based on the research results, the following research findings were obtained: e-marketing design and customer involvement capability partially have a positive and significant effect on competitive advantage. e-marketing design, customer involvement capability and competitive advantage have a positive and significant effect, partially or simultaneously, on business performance